Variability in the clinical management of iron deficiency anaemia in older adults: results from a survey of UK specialists in the care of older people - Alison I.C. Donaldson; Roy L. Soiza; Katherine J. Hands; Miles D. Witham; Phyo K. Myint (SAGE Publishing, 2019)
Background: Iron deficiency anaemia in older adults is common, but its management presents unique challenges in diagnosis and management. Little is known about compliance with current best practice guidelines. Methods: We undertook an online survey of physician members of the British Geriatrics Society to ascertain how they managed older patients with potential iron deficiency anaemia. Results: There were 141 respondents (96% from UK). Almost a third indicated they would accept haemoglobin levels <100 g/dl without further investigation. A quarter said they would only occasionally or never check ferritin levels. Only 30% would sometimes or always use parenteral iron when oral supplements were not tolerated. Conclusions: Responses suggest a high level of variation in clinical practice and low adherence to best practice guidelines. Possible explanations include an inadequate evidence base to guide management and a lack of knowledge on the challenges of managing iron deficiency anaemia in this population.